A Comparative Analysis of Planning Policies between Indonesia and Saudi Arabia during COVID-19 Pandemic - Herika Muhamad Taki (Department of Urban and Regional Planning, Universitas Diponegoro, 2021)
COVID-19 from Wuhan, China, quickly spread to all countries worldwide with the adverse effects that accompany it. Each country's response should be to provide a policy package that is swift and beneficial for people, but not all countries have policies that are as expected. This paper aims to identify any planning policy indicators through a comparative study between the two countries. This paper is hoped can formulate planning policy directions that can be applied in other countries. This study took a case study from two countries, namely Indonesia and Saudi Arabia, because they have similarities and differences, such as in the socio-cultural, physical areas, and religious fields, especially in practicing worship in the holy month of Ramadan. This research method was descriptive qualitative by using a pairwise comparison analysis that compares sustainable development factors such as social, economic, and environmental contained in the planning policies issued by each country. The result was seen similarities and differences in the policies of the two countries, and it has implemented its planning policies well but is still awaited in the next stage, namely the stages of implementation and evaluation.